Systematic review of the impact of social media on entrepreneurship - Sharma, Ravi Kant (Journal of Commerce, Management, and Tourism Studies, 2024)
In recent years, social media has developed into a powerful tool that could have a significant effect on entrepreneurial activities; however, research on this impact is still in its infancy. Therefore, the purpose of this study is to investigate the impact of social media on entrepreneurship. This study uses the systematic literature review (SLR) method. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology has been used to analyse and synthesise the findings from 20 pertinent research papers for the study. The results showed that social media has a significant impact on entrepreneurship, enabling customer interaction, effective marketing, and entrepreneurial intent, it presents risks and issues. The study’s findings provide valuable information that aids practitioners, scholars, and policymakers in understanding the dynamic relationship between social media and entrepreneurship.